Sustainability assessment of vegetable production under Cambodia's good agriculture practice (CAMGAP) in Kandal province - Ouly Thorng; Zulfiqar, Farhad; Himanshu, Sushil Kumar; Tsusaka, Takuji W.; Yaseen, Muhammad; Thai Pipe Scholarship; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
This master{u2019}s thesis aims to fulfill the knowledge gap of sustainability performance of Good Agriculture Practice (GAP) certification system by investigating sustainability status of vegetable producers who are adopted Cambodia{u2019}s GAP in Kandal province. To achieved it, this study has 3 objectives: (1) to examined the economic, social and environmental sustainability of CamGAP certified vegetable production at farm level in the study area, (2) to examined the factors effect sustainability of CamGAP adopter in Cambodia and (3) to identified the strength and weakness of CamGAP adopter. This study was quantitative research to explore the findings. Kandal Province was chosen for study area. Sample size for this study consists of 165 vegetable farmers from Sanng District and was divided into CamGAP-adopter (57) by using full population sampling and Non-CamGAP adopter or Conventional farmer (108) by using random sampling. The result from T-test showed that CamGAP farm received good to best sustainable practice in farm from green score to dark green score. Economic dimension received the highest score which was 0.80, followed by good governance (0.79), social well being dimension (0.78) and environmental integrity dimension (0.66). For overall sustainability score from 2CamGAP3 farm group was 0.76 in high sustainable value (green color). Results from fractional logistic regression have identified factors significantly affecting the overall sustainability of vegetable production in Kandal province. These significant factors including farm types, marital status, land type, off farm income and land ownership. The findings from SWOT analysis showed strengths in favorable land for cultivation with potential human resources, have low financial risk and is climate resilience farm. Weakness mostly on poor post-harvest management, low processing activity and inefficient agribusiness management skill. Opportunities addressed were continuously support from NGOs, government and development partners in financial and human resources and having room to expand the business by the demand grow. Finally, threats for CamGAP farms including niche market and product counterfeit. To improvement the sustainability performance of vegetable farmer, continuously providing assistant in agricultural information, materials and financial support and improve their knowledge in cultivation and farm management.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agribusiness Management
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Sustainable agriculture -- Management -- Cambodia; Sustainable development -- Cambodia